2016
DOI: 10.1038/srep29579
|View full text |Cite
|
Sign up to set email alerts
|

Selective local lysis and sampling of live cells for nucleic acid analysis using a microfluidic probe

Abstract: Heterogeneity is inherent to biology, thus it is imperative to realize methods capable of obtaining spatially-resolved genomic and transcriptomic profiles of heterogeneous biological samples. Here, we present a new method for local lysis of live adherent cells for nucleic acid analyses. This method addresses bottlenecks in current approaches, such as dilution of analytes, one-sample-one-test, and incompatibility to adherent cells. We make use of a scanning probe technology - a microfluidic probe - and implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 37 publications
(52 reference statements)
3
39
0
Order By: Relevance
“…Some applications of the two-aperture MFP include biopatterning surfaces, 278 delivery of reagents to reaction site, 279 selective detachment and collection of a living single cell, 278 and analyzing tissue samples. 280,281 Applications of the threeaperture and four-aperture MFPs/micropipttes have also been reported for single cell analyses, 271,282 local lysis of live adherent cells, 283 surface processing and patterning, [284][285][286] region-selective micro-treatment of cells, 287 and studying cell interactions. 288 In addition, the potential of the convective-diffusive concentration gradient 289 generated by the MFP in studying neutrophils chemotaxisphenomenon that describes the dynamic nature of the immune defense barrier against infections [290][291][292] has also been demonstrated.…”
Section: Microuidic Probesmentioning
confidence: 99%
“…Some applications of the two-aperture MFP include biopatterning surfaces, 278 delivery of reagents to reaction site, 279 selective detachment and collection of a living single cell, 278 and analyzing tissue samples. 280,281 Applications of the threeaperture and four-aperture MFPs/micropipttes have also been reported for single cell analyses, 271,282 local lysis of live adherent cells, 283 surface processing and patterning, [284][285][286] region-selective micro-treatment of cells, 287 and studying cell interactions. 288 In addition, the potential of the convective-diffusive concentration gradient 289 generated by the MFP in studying neutrophils chemotaxisphenomenon that describes the dynamic nature of the immune defense barrier against infections [290][291][292] has also been demonstrated.…”
Section: Microuidic Probesmentioning
confidence: 99%
“…[194][195][196][197][198] More recently, stagnation flows have been developed with open microfluidic systems in the form of microfluidic pipettes and probes, to collect vesicles and perform cell analysis respectively. [199][200][201][202][203][204][205] The microfluidic probe has been further developed to generate the microfluidic quadrupole trapping mechanism, which has been used to study neutrophil chemotaxis. [206,207] Detailed reviews on the application of microfluidic quadrupoles can be found in ref.…”
Section: Microparticle Tweezersmentioning
confidence: 99%
“…Zelenin et al [ 39 ] lysed all blood cells using 1% saponin but left the bacteria cells intact for analysis as the bacterial cells are unaffected by Triton X-100 and saponin. Kashyap et al [ 40 ] developed a scanning microfluidic probe to selectively lyse cells in adherent cultures. The probe injects sodium hydroxide over cells of interest using advanced hydrodynamic manipulation in order to lyse and subsequently extract the DNA and RNA that is released ( Figure 1 B).…”
Section: Lysis Techniquesmentioning
confidence: 99%
“…Adapted from [ 35 ] with permission of The Royal Society of Chemistry ( B ) Selective lysis of cells: Illustration of a microfluidic probe head skim through cells, the interaction of biochemicals with the cells (inset). Reprinted from [ 40 ] with permission of Nature Publishing Group, Copyright 2016.…”
Section: Figurementioning
confidence: 99%